Moralitas Jawa dalam Wayang Kulit Purwa: Tinjauan pada Lakon Laire Semar - Darmoko, Darmoko (Paradigma: Jurnal Kajian Budaya, 2015)
The Javanese leather puppet use myths about the gods, prophets, spirits, and people of the ancient time, besides the texts of Lokapala, Arjunasasrabahu, Ramayana, and Mahabarata to teach prudence and to enable men to respond to the happenings of their natural life, or “daya-daya kekuatan alam” (van Peursen, 1989: 37). These myths contain the moral philosophy about the relation of men with other men, with nature, and with God, determined by a pattern of thought which orients itself toward the principles of harmony and balance. The paper highlights the story of the birth of Semar, or Laire [in English: la-ee-ray} Semar, which shows how the Javanese morality was constructed and power in the Javanese conception implemented. Semar, god in human form, reveals the essence of power a king should have, and teaches that power is a godly characteristic used to enhance goodness. This concept is against the belief that power is ruthlessness and domineering that is hidden in good-look, princely manner and power. His ugly looking reflects the importance of inner strength which is generous and kind, over handsome outward look, but has a mean heart As an expression of arts, the puppeteers hold an important role to distribute the stories that have philosophical meaning to the audience when the leather puppet show was conducted. A puppeteer, after all, carries a holy role.